Vocal fold adjustments in Danish voiceless obstruent production - Hutters, Birgit (Annual Report of the Institute of Phonetics University of Copenhagen, 1984)
Vocal fold adjustments in the production of single intervocalic voiceless obstruents in Danish were investigated partly by photo-electric glottography combined with fiberoptic stills, and partly by electromyographic signals obtained from several intrinsic laryngeal muscles. The results show that the glottal opening-closing gesture, controlled by the laryngeal muscles, and its relation to the supraglottal articulation vary not only according to type of obstruent category but also within one and the same category. In the discussion I argue that in dealing with aspiration our understanding of the laryngeal mechanism involved may be hampered if we focus on the interarticulatory timing rather than on the glottal gesture as such. With regard to the glottal gesture in the unaspirated stops I assume that the opening of the glottis is a consequence of the cessation of vocal fold vibrations. However, I tend towards the view that devoicing in these stops is not only a passive process, i.e. due to the changing aerodynamic conditions induced by the oral closure, but that some additional mechanism is directly involved in the devoicing process. I venture the controversial hypothesis that the PCA and INT activity actually found in these stops is a devoicing action rather than a means to open and close the glottis. Finally, some problems relating to the interpretation of the laryngeal EMG signals with reference to obstruent production are pointed out.